2016
DOI: 10.1080/00016357.2016.1236985
|View full text |Cite
|
Sign up to set email alerts
|

Use of platelet concentrates in oral and maxillofacial surgery: an overview

Abstract: Evidences described in the literature on the efficacy of platelet concentrates in procedures in oral and maxillofacial region are controversial and limited. In order to clarify the real advantages and priorities for the patients, when the blood-derived products are applied, further in vitro and in vivo research about the activity of PRP and PRF on the dental cells biology should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 113 publications
0
25
0
11
Order By: Relevance
“…APC are a source of platelet‐derived factors obtained by sequestering and concentrating platelets by gradient density centrifugation (Del Fabbro, Gallesio, & Mozzati, ; Mihaylova et al, ). APC contain many factors that promote healing, such as adhesive proteins, pro‐coagulant factors, cytokines and chemokines, anti‐microbial proteins and growth factors such as platelet‐derived growth factor (PDGF), transforming growth factor‐beta (TGF‐b), epidermal growth factors (EGF), and vascular endothelial growth factors (VEGF) (Del Fabbro et al, ; Mihaylova et al, ). Its use in dental surgery is associated with activation of the proliferation, migration, and differentiation of cells in the wound area, especially when the number of cells in the tissue injury site is reduced, increasing the regenerative process (Mihaylova et al, ).…”
Section: Skeleton Side Effects Of N‐bps Prevention and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…APC are a source of platelet‐derived factors obtained by sequestering and concentrating platelets by gradient density centrifugation (Del Fabbro, Gallesio, & Mozzati, ; Mihaylova et al, ). APC contain many factors that promote healing, such as adhesive proteins, pro‐coagulant factors, cytokines and chemokines, anti‐microbial proteins and growth factors such as platelet‐derived growth factor (PDGF), transforming growth factor‐beta (TGF‐b), epidermal growth factors (EGF), and vascular endothelial growth factors (VEGF) (Del Fabbro et al, ; Mihaylova et al, ). Its use in dental surgery is associated with activation of the proliferation, migration, and differentiation of cells in the wound area, especially when the number of cells in the tissue injury site is reduced, increasing the regenerative process (Mihaylova et al, ).…”
Section: Skeleton Side Effects Of N‐bps Prevention and Managementmentioning
confidence: 99%
“…APC contain many factors that promote healing, such as adhesive proteins, pro‐coagulant factors, cytokines and chemokines, anti‐microbial proteins and growth factors such as platelet‐derived growth factor (PDGF), transforming growth factor‐beta (TGF‐b), epidermal growth factors (EGF), and vascular endothelial growth factors (VEGF) (Del Fabbro et al, ; Mihaylova et al, ). Its use in dental surgery is associated with activation of the proliferation, migration, and differentiation of cells in the wound area, especially when the number of cells in the tissue injury site is reduced, increasing the regenerative process (Mihaylova et al, ). Several systematic reviews have identified the use of APC as an adjunct therapy in the prevention and treatment of BRONJ in patients undergoing oral surgery, with a lower incidence on the pathology (Del Fabbro et al, ; Mihaylova et al, ).…”
Section: Skeleton Side Effects Of N‐bps Prevention and Managementmentioning
confidence: 99%
“…Due to their potential capacity to induce and enhance hard and soft tissue healing, platelet-derived concentrates are agents with great regenerative capacity, and they arereceiving a lot of attention in the field of medicine [25]. The impact of platelet-derived concentrates is the result of their large number of platelets, which includes a wide variety of growth factors and active biomolecules [25].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The impact of platelet-derived concentrates is the result of their large number of platelets, which includes a wide variety of growth factors and active biomolecules [25].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…2,9, 10 The potential role of GFs in periodontal regeneration is currently the focus of research. In recent years, there has been an increase in the scientific evidence that demonstrates their effectiveness in periodontal regeneration.…”
Section: 578mentioning
confidence: 99%